Growth of Lactobacillus paracasei SNP-2 in Peanut Milk and Its Survival in Fermented Peanut Milk Drink During Storage - Tyas Utami; Giyarto Giyarto; Titik F. Djaafar; Endang S. Rahayu (Indonesian Food and Nutrition Progress, 2014)
Fermentation of peanut milk added with various sucrose concentrations using candidate probiotic strain of Lactobacillus paracasei SNP-2 was investigated, and the lactic acid bacteria survival during storage of the fermented peanut milk drinks were also studied. Peanut milk fermentations were carried out at 37°C for 18 h. It was found that peanut milk without addition of sucrose could support the growth of L. paracasei SNP-2, but not the production of lactic acid. Fermentation of peanut milk with addition of 2-10% sucrose significantly increased the production of lactic acid. The numbers of lactic acid bacteria showed no marked reduction in the fermented peanut milk drinks during storage at 4°C for 21 days, still sufficiently high to exert beneficial probiotic effects in the host. Fermented peanut milk drink using L. paracasei SNP-2 can be used as a non-dairy probiotic product.